MENINGKATKAN MUTU UMAT MELALUI PEMAHAMAN YANG BENAR TERHADAP SIMBOL ACINTYA (PERSPEKTIF SIWA SIDDHANTA) - Widya Sena, I Gusti Made (LPM IHDN Denpasar, 2016)
God is very difficult to understand with eyes. In order to know God, His nature, and His personification, use of various symbols can be helpful, which suggests the unification of two elements, namely the physical and spiritual ones. Acintya is the symbol or manifestation of God s Omnipotence. It is the âunimaginableâ that turns to be the âimaginable